Management of Hypertensive Urgency in Outpatient Department with Oral Medications - Gautam, Samir; Barakoti, Murari; Dhungel, Sachin; KC, Bishal; Khan, Majhar; Shakya, Abhishesh; Ghimire, Jeet Prasad; Sharma, Deepanjali (Journal of National Heart and Lung Society Nepal, 2024)
Background: Hypertensive urgency is severe elevation of blood pressure without ongoing target organ damage. In our country there is tendency to admit patient and give injectable medications for the control of blood pressure. We wanted to know the feasibility and effectiveness of oral medications in outpatient basis. Methods: This is a cross-sectional observational study conducted at Gautam Buddha Community Heart Hospital. One hundred and twenty-eight patients with blood pressure more than or equal to 180 mmHg Systolic and/or 110 mmHg Diastolic attending outpatient department were evaluated in this study. Results: Distribution of patients was males 56.2 % and females 43.8 %. Most patients (48.4%) were in the age group 45 to 65 years. Headache (35.9%) and dizziness (25.7%) were common symptoms at presentation. Majority of hypertensive patients had blood pressure range 180 to 220 SBP (88.3%) and 110 to 130 DBP (78.9%). Reduction of mean arterial pressure by 20 % reached within 6 hours in 82.8%. Conclusion: Management of severe elevation of blood pressure in outpatient basis with oral medications is feasible option. This helps to build the confidence of treating physicians at rural part working under limited resources.